Seven channel wavelength demultiplexer using a tandem a:SiC-H/a:Si-H photo sensor - Silva, Vítor (2019)
The pi'npin photo device is a tandem a: SiC-H / a: Si-H heterostructures. The device is electrically biased and can also be optically biased by ultra-violet illumination of the front or back surfaces. The front surface is also used for several pulsed single wavelength signals within the visible range. Experimental results show that the ultra-violet bias illumination at the front surface of the device enhances wavelengths longer than 500 nm while quenching the wavelengths shorter than 500 nm. The opposite happens when the bias is set at the back surface of the device; wavelengths shorter than 500 nm are enhanced while the ones above are quenched. Several digital applications have been built using the p'inpin device. This paper focuses on the use of the pi'npin device for seven channel Wavelength Division Multiplexing (WDM) digital communication using Manchester coded signals, with a single wavelength for each channel. The seven channels form a frame with 7*256 bits with a preamble for signal intensity and synchronization purposes. Results show that the clustering of the received signal enables the successful recovery of the seven channel data using the front and back illumination of the surfaces of the pi'npin photo device.